Plasma Interleukin-10 Levels Are Altered in Women with Severe Premenstrual Syndrome: A Preliminary Study - Kaori Yama; Yuki Asari; Aiko Ono; Maiko Machida; Jun Miura (Women's Health Reports, 2020)
Background: The precise pathophysiology of premenstrual syndrome (PMS) is unknown, and chronic inflammation has been implicated in PMS. However, inflammatory markers, including cytokines and C-reactive protein (CRP), have not been investigated before and after menstruation in relation to PMS among the same participants. This study investigated whether the plasma levels of tumor necrosis factor-?, interleukin (IL)-6, IL-10, and CRP are related to PMS. Methods: The study included 21 healthy Japanese women (aged 19?24 years) with a regular menstrual cycle. Inflammatory marker levels in plasma were determined using enzyme-linked immunosorbent assay. In addition, the level of depressiveness was assessed using the Center for Epidemiologic Studies Depression (CES-D) scale. Results: Of the 21 women, 7 were considered to have moderate-to-severe PMS (PMS [+] group) and 14 were considered to have no or mild PMS (PMS [?]), and none of the participants had premenstrual dysphoric disorder. The IL-10 levels were significantly lower before than after menstruation in the PMS (?) group. The IL-10 levels before menstruation were significantly higher in the PMS (+) group than in the PMS (?) group. Other markers did not show relevant differences between the groups. The CES-D scores were higher in the PMS (+) group than in the PMS (?) group both before and after menstruation. There were positive correlations between the CES-D scores and IL-6 levels before menstruation and the CES-D scores and IL-10 levels after menstruation. Conclusions: The IL-10 levels before menstruation were higher in women with PMS than in those without PMS, and these levels might be related to PMS.